PENGARUH LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DEPARTEMEN PULP MAKING-2 PT.INDAH KIAT PULP & PAPER PERAWANG - Eventina Sitorus; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study aims to determine the effect of work environment on employee productivity Department of Making Pulp-2 PT.Indah Kiat Pulp & Paper, Perawang. Work environment as an independent variable (X) and labor productivity as the dependent variable (Y), and this study takes the number of respondents as many as 53 people. Data obtained through the questionnaire and then further processed to be tested through statistical analysis such as a simple regression analysis, t test, and correlation analysis and determination with the help of using SPSS 16 for windows. The results showed that the results of hypothesis testing t test, t (11,136)  t table (2.040). This suggests that the work environment have a significant effect on employee productivity. The amount of work environment on employee productivity Department of Making Pulp-2 PT.Indah Kiat Pulp & Paper is equal to 70.9%. Keywords: human resource management, work environment, work productivity.